BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN GAKY PADA WANITA USIA SUBUR (WUS) DI KECAMATAN BATURADEN KABUPATEN BANYUMAS - Dardjito, Endo; Rahardjo, Setiyowati (Publikasi Penelitian Terapan dan Kebijakan, 2010)
Iodine Deficiency Disorder (IDD) is one of nutrient problems in Banyumas Regency. IDD is caused of the lack of iodine substance continually in long period. the other causal factors are the consuming goitrogenic substance, knowledge, genetic and consuming hormonal contraception (KB). Baturraden district is one of districts in Banyumas Regency in which it has got an increase prevalence aneurysm. Based on a survey held in 2007, aneurysm prevalence was 35.38% and it was included as a high endemic. The objective of this research is to analyze somerisky factors influencing IDD in Baturraden distric. The research is an explanatory study applying control case. The case samples are the 15 – 45 year-old productive women suffering from the IDD living in Kebumen, Karang Tengah, Kemutug Kidul and Karang Salam villages. The numbersof samples are 30. The Analysis applied are the univariate, bivariate, and multivariate analysis. The result of the research shows that there are two risky factors influencing IDD namely consuming Iodine (p value=0.007) and consuming goitrogenic (p value=0.015). The most dominant factor influencing IDD is the consuming Iodine. Because of that the directive counseling should be increased to disseminate about the need of the increase on consuming iodine and decrease of consuming goitrogenic substance. This dissemination could be inserted on Posyanduand PKK activities.